2020
DOI: 10.1177/0022427820949895
|View full text |Cite
|
Sign up to set email alerts
|

Gang Affiliation and Prisoner Reentry: Discrete-Time Variation in Recidivism by Current, Former, and Non-Gang Status

Abstract: Objectives: Reentry experiences for the 600,000 people released annually from federal and state prisons differ vastly. We contend that gangs, which rose to prominence alongside mass incarceration, are an overlooked source of variation in reentry experiences. Drawing on precepts from the street gang literature, we test whether patterns of recidivism differ by official and survey measures of current, former, and non-gang status. Methods: Data from a representative sample of 802 prisoners interviewed prior to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 110 publications
(108 reference statements)
0
2
0
Order By: Relevance
“…First, even though we did not have access to correctional intelligence files on the dates gang affiliation was classified, our survey data showed that in the 6 months prior to the interview date, no respondents joined a gang and only three left. Furthermore, official reclassification to an “ex” lags behind status transitions among prisoners (see Pyrooz et al., 2021). Additionally, a range of time‐stable factors are included as controls for nonrandom selection into gangs.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…First, even though we did not have access to correctional intelligence files on the dates gang affiliation was classified, our survey data showed that in the 6 months prior to the interview date, no respondents joined a gang and only three left. Furthermore, official reclassification to an “ex” lags behind status transitions among prisoners (see Pyrooz et al., 2021). Additionally, a range of time‐stable factors are included as controls for nonrandom selection into gangs.…”
Section: Methodsmentioning
confidence: 99%
“…The outcome of interest is prison misconduct, which captures self-reported institutional rule violations in the 6 months prior to the interview. Most studies use the same sources of data to test the relationship between gang affiliation and misconduct (see Pyrooz, 2022). In our case, self-report indicators of misconduct are used as our theoretical model focuses on prisoners' behavioral responses to official gang policies and treatment as opposed to focusing on how authorities respond to reported behaviors.…”
Section: Misconductmentioning
confidence: 99%